(untitled) (Modern education and development, 2024)
This article explores the semantic features of proverbs that incorporate phytonyms in English and Uzbek, highlighting their cultural significance and the moral lessons they convey. Proverbs, as succinct expressions of collective wisdom, serve to reflect the historical, social, and environmental contexts of the cultures from which they emerge. The use of phytonyms—words derived from plants—enhances the imagery and metaphoric depth of these proverbs, linking human experiences to the natural world. In both English and Uzbek traditions, such expressions reveal universal truths about life, emphasizing themes of growth, consequence, and interdependence.